CHARACTERISTICS OF SOCIO-PROFESSIONAL GROUP OF UNIVERSITY TEACHERS IN CONDITIONS OF CHANGES IN THE SYSTEM OF HIGHER EDUCATION - M. Shmantsar (Вестник университета)
The concept of social group and its indications are considered in the article. Through a comparison with the social community the designation of university teachers as a socioprofessional group is justified. Based on empirical research results the traits of the specified group is revealed. Data analysis a questionnaire survey and in-depth interviews allows to show what changes occur in the characteristics of socio-professional group of university teachers under the influence of the transformational processes in higher education.